RELATIONSHIP BETWEEN BLOOD ANTIOXIDANT ENZYME LEVELS AND GENOTYPE DURING MIGRAINE ATTACK AND INITIAL PERIODS IN MIGRAINE PATIENTS - Ozbey, Ulku; Ozel, Seda; Berilgen, M. Said; Seyran, Ayse; Erisir, Mine (Wiley-Blackwell, 2009)
[Abstract Not Available]